Lentinus squarrosulus: precision identification through molecular method in challenging fungaemia case - Zainulabid, Ummu Afeera; Saw, Yen Tsen; Chua, Hiu Jian; Yeow, Yong Yaw; Toh, Sian Lin; Leong, Chee Loon; Khalid, Khairil Erwan; Mohamed Sukur, Salina; Suhaimi, Nadia Syahirah; Ismail, Ismaliza (Elsevier, 2024)
Fungal identification poses a formidable challenge in medical diagnostics. This case study unveils the first documented case of Lentinus squarrosulus fungemia in a 30-year-old male afflicted by retroviral disease and undergoing Highly Active Antiretroviral Therapy (HAART).